(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Papaya (Carica papaya L.) peel contains bioactive compounds like pectin, widely used in making edible films due to its gel-forming ability, offering a sustainable way to repurpose fruit waste. The reliance on synthetic plastics for packaging and the insufficient management of papaya peel waste highlights the need for a sustainable alternative. Limited research exists on how different acids used for pectin extraction affect film properties. This study focused on extracting pectin from papaya peel using hydrochloric acid (HCl) and citric acid (CA) and incorporating it into starch-based films at 0.5% and 1% concentrations. Pectin extraction efficiency was influenced by acid type, with HCl yielding 9.1%, significantly higher than CA 3.99%. The extracted pectin was characterized as high methoxyl pectin with degrees of esterification (DE) ranging from 51.82% to 52.26%. A higher acid percentage enhanced tensile strength and reduced elongation at break, improving mechanical stability. FTIR analysis confirmed pectin structures and degradation, showing a higher OH peak. Color analysis and water vapor permeability tests revealed that films with 1% pectin extracted using CA had the lowest water vapor permeability, improving moisture barrier properties. UV-Vis spectroscopy analyzed optical properties, UV-Vis spectroscopy showed that films incorporating 1% pectin extracted using HCl exhibited greater UV absorbance due to the presence of phenolic compounds, highlighting their potential as effective natural UV-blocking packaging materials while biodegradability tests showed that films incorporated with 0.5% pectin extracted using CA degraded more efficiently than the control and film incorporated with pectin extracted with HCl. In conclusion, pectin extracted using HCI more effectively than CA. Pectin extraction using HCl proved more efficient, resulting in a higher yield compared to CA. Additionally, incorporating 1% pectin extracted using CA preserves pectin’s molecular weight and functional properties, enhancing film quality in starch-based films by improving its physical and mechanical characteristics.